Building Inclusive Citizenship: A Study in Yogyakarta Societies - Usmi, Rianda; Budimansyah, Dasim; Rahmat; Siti Masyitoh, Iim; Sari, Beti Indah; Eprilianto, Deby Febriyan (Jurnal Kewarganegaraan, 2025)
The increasing intensity of socio-ethnic conflicts in the last decade in Yogyakarta has led to stereotypes and social segregation between local residents and migrants. This research aims to analyze how the Provincial Government of DIY can build inclusive citizenship in its community through Community Pancasila Education, namely the Sinau Pancasila Program. This qualitative research with a case study design was conducted in the Province of DIY. Data collection was conducted using interview, observation, and documentation techniques. Data analysis was conducted using qualitative data analysis techniques. This study found that the Sinau Pancasila Program is very important in the formation of inclusive citizenship in the DIY, namely to appreciate the nation's pluralism in order to minimize conflicts of identity, ethnicity, and socio-religion. The Provincial Government of DIY can build inclusive citizenship in its community through the Sinau Pancasila Program, which is functioned and maximised as an educational forum for community political education, a mingling forum, and a dialogue-communication forum. Sinau Pancasila Program is believed to be able to minimizing socio-ethnic conflicts and strengthening the value of diversity in the Yogyakarta. Therefore, the Sinau Pancasila program is very important for the Provincial Government of DIY to continuously implement this program.